Mendorong Aktivitas Literasi Yang Menyenangkan Di Desa Sokawati Dalam Pembelajaran Bermain - Pipit Fitriani; Siti Nariah; Dewi Maemunah; Adinda Risqiana Dewi Maulana; Aulia Kamilah Munifah; Nailil Izzah (Universitas Maritim AMNI Semarang, 2023)
Enhancing the quality of education involves fostering strong literacy skills, not only in academic aspects but also in understanding, processing, and conveying information. In the midst of globalization and technology, literacy skills have become increasingly important in facing the changes of the times. This study aims to develop a playful learning approach that encourages enjoyable literacy activities in Desa Sokawati. Employing a qualitative approach with an action research design, this study engages children, educators, parents, and the community in Desa Sokawati. Engaging literacy activities tailored to the characteristics of children are designed based on surveys and interviews. Once planned, these literacy activities are implemented in KB, TK, and SD classes. Observations of children's and educators' responses are conducted during the implementation phase. The results indicate that the playful learning approach is effective in fostering enjoyable literacy activities in Desa Sokawati. Children are engaged in various activities that combine creativity, art, and learning. By developing an approach that suits the characteristics of children and the local potential, this study aims to provide practical guidance for educators, parents, and the community in enhancing children's literacy in Desa Sokawati. Furthermore, this research contributes to the development of sustainable literacy-based education in rural areas.